Comparative study on Various Tube Voltages and Contrast Media Doses in CT Pulmonary Angiography to detect Pulmonary Thromboembolism - Abdul-Qader, Shaymaa Khalid; Fadhil, Atheer Adnan (AL-Kindy College Medical Journal, 2022)
Background: Lowering the amount of iodinated contrast material and tube voltage may increase pulmonary artery opacification and thrombus identification without compromising picture quality. Objectives: To explore the efficiency of using lower tube voltage and a lower contrast medium dose for conducting computed tomography for pulmonary angiography (CTPA) aiming to increase its accuracy in detecting pulmonary thromboembolism (PTE). Subjects and Methods:100 patients scheduled for CTPA with a preoperative diagnosis of PTE were grouped into two: group A, (50 patients) got 1 mL/kg at 120 kV and group B, (50 patients) received 0.5 mL/kg at 80 kV.The technique of bolus tracking was implemented.Values of midpoint of multiple pulmonary artery divisions were used to assess attenuation.Significant values are those that exceed 300 Hounsfield units (HU). The dosage of radiation received by the patient, defined as the effective dose, was compared between groups. Results: Total mean attenuationdata for the pulmonary arteries have shown to be substantially greater in group-B compared to group-A (39110.4HU vs. 335.97.9HU, P=0.001). Moreover, total dose length product (DLP) values were substantially lower in group-B (934.9 mGy.cm vs. 384.443 mGy.cm, P=0.001). While effective dose values have shown to be significantly lower in group-B (2.90.3 mSv vs. 13.21.8 mSv, P 0.001). Conclusion: Low-kilovoltage technique and low quantity of iodinated contrast are useful in conducting (CTPA) with high accuracy in detection of pulmonary thromboembolism.